An assessment of marital adjustment in patients with rheumatoid arthritis - Hatice Resorlu; Basak Sahin; Hulya Ertekin; Serhad Bilim; Yılmaz Savas (Medicinski glasnik, 2017)
Aim: To investigate marital adjustment in patients with rheumatoid arthritis and factors affecting this. Methods: A total of 32 patients diagnosed with Steinbrocker class 1-2 rheumatoid arthritis and 32 healthy individuals from a similar age group were included. Sociodemographic characteristics, the Beck Depression Inventory (BDI), short-form 36(SF-36) and the dyadic adjustment scale (DAS) were evaluated in both groups. A visual analogue scale (VAS), the disease activity score 28 (DAS28) and a health assessment questionnaire (HAQ) were also investigated in the patient group. Results: Mean ages were 46.5±9.2 years in the patient group and 47.7±8.1 in the control group (p=0.5). No significant difference was determined between the two groups in terms of sociodemographic characteristics. No statistically significant correlation was observed between erythrocyte sedimentation rate (ESR), patient and physician global VAS, DAS28, HAQ and morning stiffness and DAS total score. Comparison of DAS subunits revealed a significant difference in dyadic satisfaction and affectional expression in the patient and control groups (p=0.046 and p=0.037). A statistically significant negative correlation was observed between duration of the disease and marital adjustment (p=0.01;r= -0.58). Conclusion: Due to its progressive and prolonged course rheumatoid arthritis can also affect individuals’ social relationships besides restricted daily living activities. Activation of rheumatoid arthritis did not affect marital adjustment in this study, but adjustment decreased with duration of the disease.
Keywords: marital relationship; rheumatic disease; disease activity